2008
DOI: 10.5964/ijpr.v2i1.17
|View full text |Cite
|
Sign up to set email alerts
|

The Endurance of Love: Passionate and Companionate Love in Newlywed and Long-Term Marriages

Abstract: Most theorists assume that the passage of time will have a very different impact on passionate versus companionate love. Passionate love is said to decline fairly quickly, while companionate love is thought to remain fairly stable (or actually increase) over time.This hypothesis was tested in two studies. In Study 1, we interviewed 53 newlywed couples soon after their marriages and again one year later, when presumably (for some) the "honeymoon was over." In Study 2, we interviewed a random sample of 240 older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
2
67
2
4
Order By: Relevance
“…Comparing younger and older adults seeking a new relationship provides a more equivalent starting point than comparing long-time married couples to newlyweds. Older adults tend to have longer relationships, which in turn are associated with declining sexual, passionate and friendship-based, companionate love (Hatfield, Pillemer, O'Brien, & Le, 2008). In this lifespan sample of eHarmony users all looking to pursue a new relationship, the relative importance of sexual attraction was still lower in later life, and not as a function of relationship duration.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing younger and older adults seeking a new relationship provides a more equivalent starting point than comparing long-time married couples to newlyweds. Older adults tend to have longer relationships, which in turn are associated with declining sexual, passionate and friendship-based, companionate love (Hatfield, Pillemer, O'Brien, & Le, 2008). In this lifespan sample of eHarmony users all looking to pursue a new relationship, the relative importance of sexual attraction was still lower in later life, and not as a function of relationship duration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after stating that the Storge subscale of the LAS measures an individual's love style of merging friendship and love, Hendrick & Hendrick (1986) comment: "There is no fire in storgic love; it is solid, down-to-earth, and presumably enduring" (p. 400). However, a rare longitudinal study that measured Companionate Love in newlywed couples shortly after marriage and one year later found that it had declined for both husbands and wives in the same degree that their Romantic Love had declined (Hatfield et al 2008). The presumed endurance of Companionate Love deserves further test, for the causal conditions conducive to liking and friendship are not impervious to changes in the partners as a result of changes in their social and physical environments.…”
Section: Companionate Lovementioning
confidence: 99%
“…People who are in love are more likely to give and receive oral sex, as well as to engage in sexual activity in general, compared to people who are not in love (Kaestle and Halpern 2007;Regan 2000). Although passionate love typically wanes through the course of a relationship (Hatfield et al 2008), if a couple is able to sustain passionate love (e.g., by engaging in novel and arousing activities; Aron et al 2000), then relationship satisfaction will increase.…”
Section: The Joys Of Lovementioning
confidence: 99%
“…Like passionate love, however, companionate love can also decrease over time in relationships (Hatfield et al 2008) and then its benefits decline too.…”
Section: The Joys Of Lovementioning
confidence: 99%